An FMRI meta-analysis of interoception in eating disorders - Nandini Datta; Anna Hughes; Mattia Modafferi; Megan Klabunde (NeuroImage)
Eating Disorders (EDs) are associated with disturbed interoception – the sense of the internal condition of the body. Disturbances in interoception across senses have not yet been comprehensively examined in EDs. To do so, we employed an innovative Bayesian author-topic model approach to fMRI meta-analyses that pools together neural deficits across interoceptive senses and task types in participants with and recovered from EDs. Following PRISMA guidelines, our results combine activation patterns from 1,341 initially screened studies and data from 25 manuscripts that met study criteria that compare 463 patients with EDs (current or recovered) to 450 healthy control participants (HC). Altered brain activity was found within vision/sensory processing (precuneus), taste/self-referential processing (claustrum/posterior insula) and reward/set-shifting (global pallidus, medial frontal gyrus, anterior cingulate, precentral gyrus and parietal lobe) components in EDs compared to HC. Our results reveal separate components for bottom-up exteroceptive and interoceptive processing centering around the precuneus and claustrum/insula and also reward processing/set-shifting deficits. Thus, bottom-up sensory and reward processing are key deficits in EDs during ill and recovered states.